Hypokinetic hypertrophic cardiomyopathy: clinical phenotype, genetics, and prognosis - Yishay Wasserstrum; José M. Larrañaga‐Moreira; Cristina Martinez‐Veira; Edward Itelman; Dor Lotan; Avi Sabbag; Rafael Kuperstein; Yael Peled; Dov Freimark; Roberto Barriales‐Villa; Michael Arad (ESC Heart Failure, 2022)
Abstract Aims To describe the phenotype, genetics, and events associated with the development of hypertrophic cardiomyopathy (HCM) with reduced ventricular function (HCMr). Heart failure in HCM is usually associated with preserved ejection fraction, yet some HCM patients develop impaired systolic function that is associated with worse outcomes. Methods and results Our registry included 1328 HCM patients from two centres in Spain and Israel. Patients with normal baseline ventricular function were matched, and a competing‐risk analysis was performed to find factors associated with HCMr development. Patient records were reviewed to recognize clinically significant events that occurred closely before the development of HCMr. Genetic data were collected in patients with HCMr. A composite of all‐cause mortality or ventricular assist device (VAD)/heart transplantation was assessed according to ventricular function. Median age was 56, and 34% were female patients. HCMr at evaluation was seen in 37 (2.8%) patients, and 46 (3.5%) developed HCMr during median follow up of 9 years. HCMr was associated with younger age of diagnosis, poor functional class, and ventricular arrhythmia. Atrial fibrillation, pacemaker implantation, and baseline left ventricular ejection fraction (LVEF) of ≤55% were significant predictors of future HCMr development, while LV obstruction predicted a lower risk. Genetic testing performed in 53 HCMr patients, identifying one or more pathogenic variant in 38 (72%): most commonly in myosin binding protein C (n = 20). Six of these patients had an additional pathogenic variant in one of the sarcomere genes. Patients with baseline HCMr had a higher risk (hazard ratio 6.4, 4.1–10.1) for the composite outcome and for the individual components. Patients who developed HCMr in the course of the study had similar mortality but a higher rate of VAD/heart transplantation compared with HCM with normal LVEF. Conclusions Hypertrophic cardiomyopathy with reduced ejection fraction is associated with heart failure and poor outcome. Arrhythmia, cardiac surgery, and device implantation were commonly documented prior to HCMr development, suggesting they may be either a trigger or the result of adverse remodelling. Future studies should focus on prediction and prevention of HCMr.